(3GdJMOjGJ GdHjFjI Hjf GdEWGQ GdYQHj hGdOhdj (B/s - (3TYK, YHO Gddg fhGQs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2024)
(3jJfGhd cJGH (B((3dJMOjGJ GdHjFjI Hjf GdEWGQ GdYQHj hGdOhdj(B) (3hGdPj bGeg HJCdjag (B((3OcJhQ YHO Gddg fhGQ TYK(B) (3aj MhGdj (B(499) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3MeGjI GdHjFI aj GdbGfhf GdOhdj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3efbSe Edi HGHjf GdHGH GdChd (B: (3GdbOQGJ GdHjFjI aj GdeLGd GdOhdj, GdHGH GdKGfj (B: (3GdChVGY GdHjFjI aj GdhWf GdYQHj(B.s
(3HHdjhLQGajI (B: (3UaMI (B485-491.s
Keywords: (3MeGjI GdHjFI (B((3bGfhf Ohdj(B)s; (3MeGjI GdHjFIs -- (3bhGfjf hJTQjYGJs